Desain dan Implementasi Sistem Informasi Data Potensi SAR Pada Kantor Pencarian dan Pertolongan Kelas B Gorontalo - Ali, Megiva Setyawati; Suleman, Siti Wahyuni; Polin, Muchlis; Pakaya, Nikmasari; Sabiku, Sri Ariyanti (Gorontalo State University, 2025)
The Gorontalo Class B Search and Rescue Office (KPP), as one of the technical operational units under the National Search and Rescue Agency (Basarnas), plays a crucial role in managing search and rescue (SAR) operations across Gorontalo Province. However, the current data management process for SAR potential resources is still done manually, leading to various challenges such as input errors, document loss, and difficulties in monitoring and updating information. This study aims to design and implement a web-based Information System for Potential Resources of the Gorontalo Search and Rescue Office (siDAPOG), which can accelerate, simplify, and improve the quality of SAR potential data management. The research employs a prototyping development method through five main stages: communication, quick planning, quick design modeling, prototype construction, and deployment, delivery, and feedback. The development process is iterative to ensure the system meets user requirements. The outcome is a web-based information system comprising three modules: master data, potential validation, and reporting. The system enables effective management of SAR potential participants, training types, and provides comprehensive reports for management. Testing results indicate that the system is effective in inputting, storing, monitoring, and accessing SAR potential data.